The Validity Of Interfaith Marriage Carried Out According To Catholic Religious Procedures Based On The Marriage Law - Wijaya, Mustika Mega; Lathif, Nazaruddin; DP, Sapto Handoyo (PALAR (Pakuan Law review), 2025)
Abstrak Perkawinan ialah ikatan lahir bathin antara seorang pria dengan seorang wanita sebagai suami-istri dengan tujuan membentuk keluarga (rumah tangga) yang bahagia dan kekal berdasarkan Ketuhanan Yang Maha Esa. Pada umumnya, perkawinan dilaksanakan diantara calon suami-istri yang seagama, namun dalam realitanya terdapat perkawinan beda agama yang tidak sedikit menimbulkan permasalahan tersendiri tentang keabsahannya.d Jenis penelitian yang dipergunakan adalah penelitian normatif yaitu penelitian dengan mengkaji dan mempelajari data sekunder (kepustakaan). Keabsahan perkawinan beda agama yang dilakukan dengan ajaran tata cara ajaran agama Katolik berdasarkan hukum positif di Indonesia dapat dinyatakan sah melalui penetapan pengadilan sebelum berlakunya Surat Edaran Mahkamah Agung (SEMA) Nomor 2 Tahun 2023 tentang Petunjuk bagi Hakim dalam Mengadili Perkara Permohonan Pencatatan Perkawinan Antar-Umat Beragama yang Berbeda Agama dan Kepercayaan. Akibat hukum pernikahan beda agama berdasarkan Undang-Undang Perkawinan dan hukum positif di Indonesia terlebih setelah berlakunya Surat Edaran Mahkamah Agung (SEMA) Nomor 2 Tahun 2023 tentang Petunjuk bagi Hakim dalam Mengadili Perkara Permohonan Pencatatan Perkawinan Antar-Umat Beragama yang Berbeda Agama dan Kepercayaan maka perkawinan tersebut tidak dapat disahkan oleh pengadilan, dan selanjutnya maka Dinas Kependudukan dan Pencatatan Sipil tidak dapat mencatatkan perkawinan beda agama, meski secara hukum agama Katolik telah dinyatakan sah melalui terpenuhinya dispensasi sebagaimana dipersyaratkan. Kata Kunci: Beda Agama, Perkawinan, Keabsahan Abstract Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the belief in the Almighty God. In general, marriages are carried out between prospective husband and wife who share the same religion, but in reality there are inter-religious marriages which give rise to quite a few problems regarding their validity. The type of research used is normative research, namely research by reviewing and studying secondary data (library). The validity of interfaith marriages carried out in accordance with the teachings of Catholic religious teachings based on positive law in Indonesia can be declared valid through a court decision before the Supreme Court Circular Letter (SEMA) Number 2 of 2023 comes into force concerning Instructions for Judges in Adjudicating Cases on Applications for the Registration of Interfaith Marriages Religions of Different Religions and Beliefs. As a result of the law of interfaith marriages based on the Marriage Law and positive law in Indonesia, especially after the enactment of the Supreme Court Circular Letter (SEMA) Number 2 of 2023 concerning Instructions for Judges in Adjudicating Cases of Applications for Registration of Marriages Between Religious People of Different Religions and Beliefs, marriages This cannot be ratified by a court, and furthermore, the Population and Civil Registration Service cannot register interfaith marriages, even though legally the Catholic religion has been declared valid through the fulfillment of dispensations. as required. Keywords: Different Religions, Marriage, Legitimacy.